High performance active filtering solutions for modern aircraft power network - Liu, Jun yi (2011)
In the past 2 decades the increasing intensive use of non-linear loads has resulted in a substantial reduction of power quality in electric power systems. Current harmonics produced by non-linear loads, such as power electronic converters and electrical drives cause a number of problems in power distribution networks. In more recent years this problem has affected also smaller distribution grids like for example in aircrafts, due to the so called "more electric aircraft" trend, consisting in the replacement of most of hydraulic/pneumatic actuators with electronically controlled electromechanical devices. Electrically powered actuation is becoming more attractive due to technology advances in bespoke equipment among which electrical motors, magnetic materials, electronic control circuits and power devices. Power electronics converters are required to control electrical power and are necessary for example for actuator motor drives and to convert variable frequency (360-800Hz) in the next generation of civil aircraft to a constant frequency supply bus for various loads or to a DC supply bus. Although the presence of electrically powered equipment is desirable for weight and fuel cost reduction, the increase of electrical systems on board, and above all the presence of power electronic subsystems, brings severe challenges to aircraft power system distribution interns of power quality.